Welding of defects in cast cases of turbines with perlite electrodes without heating and thermal processing - Efimenko, N.G.; Artyomova, S.V. (Вопросы атомной науки и техники, 2020)
The regularities of structural formation of the weld metal and HAZ during multilayer welding, made by the transverse humping method, with short sections of defects on cast steel 15Kh1M1FL with perlite electrodes without heating and heat treatment are considered. It has been established that the structure of all the studied zones of the welded joint is represented by upper granular bainite of varying degrees of dispersion. The difference in the hardness of the structures in the upper and middle parts of the welded joint is insignificant (3I4 and 296 HV, respectively). In the upper part, the formation of a hypereutectoid ferrite is found, which is located along the grain boundaries, which is also related with edge effect. The plastic properties of the weld metal are increased by more than 1.5 times, KCV – by more than 3 times in comparison with the base metal. Розглянуто закономірності структуроутворення металу шва і зони термічного впливу (ЗТВ) при багатошаровій заварці короткими ділянками дефектів на литій сталі 15Х1М1ФЛ перлітними електродами способом поперечної горки (СПГ) без підігріву і термічної обробки. Встановлено, що структура усіх досліджуваних зон зварного з’єднання представлена верхнім зернистим бейнітом різної міри дисперсності. Різниця в твердості структур у верхній і середній частинах зварного з’єднання незначна (314 і 296 HV відповідно). У верхній частині виявлено формування доевтектоїдного фериту, розташованого по межах зерен, що пов’язано, в тому числі, з крайовим ефектом. Пластичні властивості металу шва збільшені більш ніж у 1,5 рази, KCV – більш ніж у 3 рази в порівнянні з основним металом. Рассмотрены закономерности структурообразования металла шва и зоны термического влияния (ЗТВ) при многослойной заварке короткими участками дефектов на литой стали 15Х1М1ФЛ перлитными электродами способом поперечной горки (СПГ) без подогрева и термической обработки. Установлено, что структура всех исследуемых зон сварного соединения представлена верхним зернистым бейнитом различной степени дисперсности. Разница в твердости структур в верхней и средней частях сварного соединения незначительна (314 и 296 HV соответственно). В верхней части обнаружено формирование доэвтектоидного феррита, располагающегося по границам зерен, что связано, в том числе, с краевым эффектом. Пластические свойства металла шва увеличены более чем в 1,5 раза, KCV – более чем в 3 раза по сравнению с основным металлом.